Chemical analysis of the essential oils from Schizogyne sericea growing in different areas of Tenerife (Spain). (April 2016) - Zorzetto, Christian; Sánchez-Mateo, Candelaria C.; Rabanal, Rosa M.; Iannarelli, Romilde; Maggi, Filippo
Abstract: Schizogyne sericea, also known as 'salado', is a halophytic species widespread throughout all the Canary Islands (Spain), being more common in Tenerife and Gran Canaria. The plant has been traditionally used as analgesic, astringent, anti-inflammatory and vulnerary. The aim of this work was to investigate the chemical variability in the volatile profiles obtained from the flowering aerial parts of S. sericea harvested in different localities (Palm Mar, Los Roques and La Barranquera) of Tenerife characterized by different microclimates. For the purpose, the essential oils were hydrodistilled from the dried aerial parts by a Clevenger-type apparatus and analysed by GC–MS. A similar chemical composition for the essential oil samples from the different geographic areas was obtained. The aromatic monoterpene hydrocarbon p -cymene (43.0–57.0%) was by far the main component of the essential oils, with minor amounts of isobornyl acetate (4.5–11.0%), limonene (4.7–5.6%), β-pinene (0.7–5.3%), α-phellandrene (2.2–4.8%) and camphene (1.8–4.5%). Interesting to note was the occurrence of thymol derivatives. That may be considered important chemotaxonomic markers of the genus Schizogyne, and, more in general, of the tribe Inulae. The volatile chemical profile obtained for S. sericea was similar to that of Schizogyne glaberrima previously studied. Graphical abstract: Highlights: Schizogyne sericea is a medicinal plant endemic to Canary Islands. The essential oil obtained from three populations was analysed. p -cymene and thymol derivatives are marker compounds.